Novel Modifications and Delivery Modes of Cyclic Dinucleotides for STING Activation in Cancer Treatment - Lu Y; Li Z; Zhu X; Zeng Q; Liu S; Guan W (International Journal of Nanomedicine)
Yanjun Lu,1,* Zhiyan Li,2,* Xudong Zhu,1 Qingwei Zeng,1 Song Liu,1 Wenxian Guan1 1Division of Gastric Surgery, Department of General Surgery, Nanjing Drum Tower Hospital, the Affiliated Hospital of Nanjing University Medical School, Nanjing, People’s Republic of China; 2Division of Thoracic Surgery, Nanjing Drum Tower Hospital, the Affiliated Hospital of Nanjing University Medical School, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Song Liu; Wenxian Guan, Email liusong@nju.edu.cn; guan_wenxian@sina.comAbstract: The microenvironment tends to be immunosuppressive during tumor growth and proliferation. Immunotherapy has attracted much attention because of its ability to activate tumor-specific immune responses for tumor killing. The cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway is an innate immune pathway that activates antitumor immunity by producing type I interferons. Cyclic dinucleotides (CDNs), produced by cGAS sensing cytoplasmic abnormal DNA, are major intermediate activating molecules in the STING pathway. Nowadays, CDNs and their derivatives have widely worked as powerful STING agonists in tumor immunotherapy. However, their clinical translation is hindered by the negative electrical properties, sensitivity to hydrolytic enzymes, and systemic toxicity. Recently, various CDN delivery systems have made significant progress in addressing these issues, either through monotherapy or in combination with other treatment modalities. This review details recent advances in CDNs-based pharmaceutical development or delivery strategies for enriching CDNs at tumor sites and activating the STING pathway.Keywords: cyclic dinucleotides, stimulator of interferon genes pathway, immunotherapy